Managing attention and productivity in distracting mediated workspaces: a research path for multitasking in mediated environments - Xiong, Shili; Duff, Brittany (2020)
ABSTRACT The rapid shift to remote working environments due to the COVID-19 pandemic is forcing people to work in a mediated workspace that causes (in)attention and productivity issues. Previous attention research mainly revealed that divided attention and simultaneously conducting multiple tasks are cognitively harmful to task performance. In this paper however, we use a media psychology perspective to rethink the cause, process, and outcomes of multitasking, and propose a counterintuitive notion that strategic distraction could potentially be beneficial in a mediated workspace: (1) strategically adding another task can motivate people to continue their current work by stimulating emotion; (2) during the multitasking process, the additional task can "herd" attentional resources and inhibit task-irrelevant distractions; (3) new measures that evaluate the breadth of multitask processing (e.g., creativity, flexibility) might reveal beneficial outcomes that wouldn’t be discovered in a single-task condition. Future directions of the multitasking research should systematically connect causes, processes, and outcomes together rather than looking at them in isolation. Keywords attention, productivity, multitasking, secondary task, process, cause and effects ABOUT THE AUTHOR/S Shili Xiong University of Illinois at Urbana-Champaign sxiong9@illinois.edu Brittany Duff University of Illinois at Urbana-Champaign bduff@illinois.edu New Future of Work 2020, August 3–5, 2020 © 2020 Copyright held by the owner/author(s).